An Emergent Role for Mitochondrial Bioenergetics in the Action of Snake Venom Toxins on Cancer Cells - Urra, Félix A.; Vivas-Ruiz, Dan E.; Sanchez, Eladio Flores; Araya-Maturana, Ramiro (Frontiers in Oncology, 2022)
Beyond the role of mitochondria in apoptosis initiation/execution, several mitochondrial adaptations support the metastasis and chemoresistance of cancer cells. This highlights mitochondria as a promising target for new anticancer strategies. Emergent evidence suggests that some snake venom toxins, both proteins with enzymatic and non-enzymatic activities, act on the mitochondrial metabolism of cancer cells, exhibiting unique and novel mechanisms that are not yet fully understood. Currently, five toxin classes (L-amino acid oxidases, thrombin-like enzymes, secreted phospholipases A2, three-finger toxins, cysteine-rich secreted proteins, and snake C-type lectin) have been described by altering the mitochondrial bioenergetics. These toxins act through Complex IV activity inhibition, OXPHOS uncoupling, ROS-mediated permeabilization of inner mitochondrial membrane (IMM), IMM reorganization by cardiolipin interaction, and mitochondrial fragmentation with selective migrastatics and cytotoxic effects on cancer cells. Notably, selective internalization and direct action of snake venom toxins on tumor mitochondria can be mediated by plasm membrane proteins overexpressed in cancer cells such (e.g. nucleolin) or facilitated by the elevated Δψm of cancer cells compared to that non-tumor cells. In this latter case, selective mitochondrial accumulation of compounds linked to cationic snake peptides in a Δψm-dependent manner may be explored for new anti-cancer drug delivery systems. This review analyzes the effect of snake venom toxins on mitochondrial bioenergetics of cancer cells, whose mechanisms of action may offer the opportunity to develop new anticancer drugs based on toxin scaffolds.